Prospectivity of application of metal-carbon contact strips for current collection on Russian railways - V. Ya. Berent (Вестник Научно-исследовательского института железнодорожного транспорта)
The article considers the experience of using contact currents, the carbon strips are intensively heated, causing softening strips from carbon materials in slides of current collectors of elec-of the contact wire and its electroerosive wear. It is proposed to retric locomotives with the purpose of reducing the wear of both the duce the intensity of these phenomena by approximating the eleccontact wire and the current collectors themselves. The electrical trical contact to symmetry. Approximation to the symmetrical eleccontact made of copper and carbon materials from which the strips trical contact of the wire and the slide of the current collector was are made is not symmetrical due to the large differences in their achieved by metallization of the carbon strips. The most effective physical properties. In connection with this, when collecting high insert samples are made by the technology of impregnation of the carbon matrix with copper. Such strips showed high arc resistance and wear resistance as a result of bench tests and operational tests. Experimental operation of electric locomotives with various types of strips was carried out when working on the sections of the Murmansk branch of the October Railway on a constant and then alternating current basis. Numerous studies and operational experience have shown that with a high current load from 1200 to 1800 A, it is economically feasible to use exclusively copper-carbon strips, with lower currents up to 1050 A - purely carbon ones.